Evaluasi kepuasan pengguna arkas dengan metode eucs dan pieces (studi kasus : Kecamatan Nagrak) - Rohmat Rohmat; Arny Lattu; Mupaat Mupaat (Jurnal Pendidikan Informatika dan Sains, 2022)
The School Activity and Budget Plan Application (ARKAS) is an information system that utilizes information and communication technology to facilitate schools in managing planning, budgeting, implementation, and administration as well as accountability for BOS funds in digital form. This Application was first launched by the Ministry of Education in 2020. This study was conducted to determine the satisfaction of ARKAS users at the elementary school level in Nagrak sub-district, Sukabumi district. Measurement of the data that has been collected is done using the SmartPLS application. From the result of research with ten hypotheses, eight of them were rejected and the remaining variable were accepted. The result of control and format variable are positive on user satisfaction and the remaining variables, namely performance, information, efficiency, service, content, accuracy, ease of use, and timeliness have a negative effect on ARKAS user satisfaction.